Playground-related Extremity Fractures in an Asian Setting over the Last Decade - Are We Safe? - Kenneth Pak Leung Wong; Jeannie Leh Ying Wong; Arjandas Mahadev (Springer, 2019)
The cost of playground-related injuries remains significant. Measures adopted to prevent such fractures or reduce their severity would translate into appreciable financial savings. Our study looks at the changes in playground-related extremity fracture epidemiology over the past decade after the implementation of latest playground standards. This is a retrospective case series approved by the local ethics board comparing the results of two descriptive studies; one conducted prior to the implementation of the Singapore Productivity and Standards Board Singapore Standards SS 457: 2007 and the other thereafter. The demographics have remained the same. The proportion of public playground injuries has fallen significantly from 89.6% to 76.3% (p < 0.05), whereas school playground injuries have risen from 5.9% to 18.0% (p < 0.05). Fractures related to monkey bars and the flying fox have shown a significant improvement, decreasing to 38.1% from 47.6% (p < 0.05) and 1% from 6.9% (p < 0.05), respectively. There has been a decrease of 33% in playground-related injuries. The total financial cost of sustaining one playground-related extremity fracture has generally increased by 50%. However, considering the 37.4% drop in surgeries, the actual overall costs to the healthcare system have essentially fallen. Safety standards have had a positive effect on playground safety in Singapore. There are now fewer and less severe playground-related extremity fractures.